Tagespflege: Wer nutzt sie und wer möchte sie nutzen? Multivariable Analyse der aktuellen und zukünftigen Inanspruchnahme der Tagespflege bei der häuslichen Pflege - Bösl, Sophia; Diehl, Kristina; Pendergrass, Anna; Grässel, Elmar (Gesundheitswesen, Supplement, 2024)
Background Adult day care serves to ease the burden on informal caregivers and to provide adequate care and support for care recipients. Across Bavaria and Germany, adult day care is attended by 4 % of all care recipients. The aim of the secondary analysis was to identify variables linked to the current or desired future use of adult day care services. Methodology For the cross-sectional study Benefits of Being a Caregiver (“Zugewinne durch die Pflege”), informal caregivers of geriatric care receiver were surveyed in Bavaria from October 2019 to March 2020 (age > 65; n = 958). Data regarding caregiving situation, characteristics of informal caregivers and care recipients, and sociodemographic information were collected. Two binary logistic regression analyses were conducted to identify predictors of current or desired adult day care service use. Results Adult day care was used by 7.3 % (n = 70) of informal caregivers. Utilization was associated with dementia and high care degree requirements of the care recipient(Nagelkerke's R2 = 0.200). Of the 888 informal caregivers not using adult day care services, 223 (25.1 %) expressed a desire to use them. This was associated with care recipients suffering from dementia, a poor previous relationship, and a high subjective burden on the informal caregiver (Nagelkerke’s R2 = 0.083). Conclusion The utilization rate of adult day care was found to be higher than reported in Bavarian or German care statistics. Dementia and an increased need for care of the care recipient were associated with utilization, but contrary to reports in literature, no association with everyday limitations, sex, education, or duration of care was found. More than two-thirds of Bavarian informal caregivers do not want to use adult day care services either now or in the future.
CRIS-Team Scopus Importer:2024-03-08
Keywords: adult day care centers; care recipient; informal caregivers; long-term care